2021
DOI: 10.1016/j.aninu.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Xylooligosaccharide attenuates lipopolysaccharide-induced intestinal injury in piglets via suppressing inflammation and modulating cecal microbial communities

Abstract: Xylooligosaccharide (XOS) has been considered to be an effective prebiotic, but its exact mechanisms remain unknown. This research was conducted to evaluate the effects of XOS on pig intestinal bacterial community and mucosal barrier using a lipopolysaccharide (LPS)-caused gut damage model. Twenty-four weaned pigs were assigned to 4 treatments in a 2 × 2 factorial design involving diet (with or without XOS) and immunological challenge (saline or LPS). After 21 d of feeding 0% or 0.02% commercial XOS product, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…In the present study, we also observed that EA administrations alleviated microvilli shedding and crypt hyperplasia, as well as increased the number of goblet cells in piglets injected with PQ, which is consistent with previous studies [ 51 ]. Oxidative stress can cause the intestinal barrier injury mainly manifested as villi shorting, crypt hyperplasia, and goblet cells apoptosis, which contribute further to a reduced ability for nutritional absorption and presentation of pathogens [ 62 , 63 ]. Maintaining intestinal integrity is a prerequisite to ensure the intestinal barrier function [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also observed that EA administrations alleviated microvilli shedding and crypt hyperplasia, as well as increased the number of goblet cells in piglets injected with PQ, which is consistent with previous studies [ 51 ]. Oxidative stress can cause the intestinal barrier injury mainly manifested as villi shorting, crypt hyperplasia, and goblet cells apoptosis, which contribute further to a reduced ability for nutritional absorption and presentation of pathogens [ 62 , 63 ]. Maintaining intestinal integrity is a prerequisite to ensure the intestinal barrier function [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diversity and evenness of microorganisms in the DIA group decreased significantly, while Bacteroidetes increased significantly and Firmicutes decreased significantly. The ratio of Firmicutes and Bacteroidetes could often reflect the health situation in the colon [ 24 , 25 ]. In healthy individuals, the index of Firmicutes / Bacteroidetes (F/B > 1) is usually high, and an imbalance in the F/B index can lead to an inflammatory response [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological examination of colon tissues was carried out as reported previously [ 9 ]. Briefly, the colons were removed, fixed, and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical analysis was carried out following our previous study [ 9 ]. Briefly, the sections of the colon were incubated with primary antibodies specific to occludin (Abcam, ab216327), claudin-1 (Abcam, ab180158), and ZO-1 (Abcam, ab221546) for 60 min, followed by incubation with secondary antibody and streptavidin-biotin peroxidase for 120 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation